2004
DOI: 10.1257/002205104773558056
|View full text |Cite
|
Sign up to set email alerts
|

Trade Liberalization and Poverty: The Evidence So Far

Abstract: This paper assesses the current state of evidence on the impact of trade policy reform on poverty in developing countries. There is little empirical evidence addressing this question directly, but a lot of related evidence on specific aspects. We summarize this evidence using an analytic framework addressing four key areas: economic growth and stability; households and markets; wages and employment and government revenue. Twelve key questions are identified and empirical studies and results are discussed. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
140
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 684 publications
(144 citation statements)
references
References 122 publications
1
140
0
3
Order By: Relevance
“…increase in openness is associated with about a 0.1 improvement in the level of the human development index -almost 20 percent of the mean. The explanation here is that trade reforms in Asian economies have created new markets with diversified commodities and better access to products, and thus improved consumer welfare (Winters et al, 2004).…”
Section: Results Inmentioning
confidence: 99%
“…increase in openness is associated with about a 0.1 improvement in the level of the human development index -almost 20 percent of the mean. The explanation here is that trade reforms in Asian economies have created new markets with diversified commodities and better access to products, and thus improved consumer welfare (Winters et al, 2004).…”
Section: Results Inmentioning
confidence: 99%
“…He argued that urban poverty in India had declined and income inequality had increased significantly during the 1990s, when some policy changes with regard to trade and exchange rates had been implemented. Winters, McCulloch and McKay (2004) summarized a number of studies that discussed the role of trade liberalization in poverty reduction. Their survey indicated that although trade liberalization might work through many channels, the outcome depended on a number of factors, including the starting point of reform, the precise trade reform undertaken, the characterization of the poor and the way they sustained it.…”
Section: (B)mentioning
confidence: 99%
“…Mookherjee and Ray (2006) give a useful overview of the literature on development and endogenous inequality based on such a division. Winters et al (2004) give an overview of evidence on the relation between trade and inequality, Cline (1997) summarizes different theoretical effects of trade on income distribution, while Claessens and Perotti (2005) provide references for the links between finance and inequality, presenting theories which suggest both equalizing effects as well as the opposite. We will discuss some of the suggested mechanisms in more detail in Section 2 below.…”
Section: Introductionmentioning
confidence: 99%